Molecular architecture of polycomb repressive complexes - Chittock, Emily; Müller, Christoph W. (Biochemical Society transactions, 2017)
The polycomb group (PcG) proteins are a large and diverse family that epigenetically repress the transcription of key developmental genes. They form three broad groups of polycomb repressive complexes (PRCs) known as PRC1, PRC2 and Polycomb Repressive DeUBiquitinase, each of which modifies and/or remodels chromatin by distinct mechanisms that are tuned by having variable compositions of core and accessory subunits. Until recently, relatively little was known about how the various PcG proteins assemble to form the PRCs; however, studies by several groups have now allowed us to start piecing together the PcG puzzle. Here, we discuss some highlights of recent PcG structures and the insights they have given us into how these complexes regulate transcription through chromatin.